Balancing work and solidarity in the Western Democracies - Ron Haskins (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
The capitalist democracies of western Europe and the U.S. have developed extensive social programs, based on the principle of solidarity, that provide assistance to the destitute, the unemployed, the sick, the disabled, and the elderly. Due in part to growing levels of spending on these solidarity programs that may threaten financial solvency in some of these countries and in part to a growing belief that social programs should help people work and achieve self-sufficiency, these countries have implemented work activation policies that try to encourage, entice, and cajole physically-able people to work. Experience implementing such work activation policies now suggests that policy can emphasize the relatively new goal of work activation while still achieving the traditional social purpose of solidarity programs by greatly reducing poverty. The aim of this paper is to review the experiences of the U.S. and selected European nations in attempting to balance solidarity with work activation by discussing both the components of an ideal work activation system and the problems these systems often encounter. The problems examined include too few jobs, recessions, low wages, and disconnected adults. The overarching purpose of the paper is to find a balance between the goals of social solidarity and work activation.
Keywords: 330; Familie-Beruf; Arbeitsverhalten; Erwerbstätigkeit; Berufliche Integration; Solidarität; Arbeitsmarktpolitik; USA; EU-Staaten